DP4+App: Finding the Best Balance between Computational Cost and Predictive Capacity in the Structure Elucidation Process by DP4+. Factors Analysis and Automation - Franco, Bruno A. (2023)
Fil: Franco, Bruno A. Pontificia Universidad Católica Argentina. Facultad de Química e Ingeniería del Rosario. Instituto de Investigaciones en Ingeniería Ambiental, Química y Biotecnología Aplicada; Argentina